Characteristics and Quality of Germplasm Resources in P. niruri from Different Source - F. Niu1, Ying; Y. Tang1, De; L. Li1, Xue; W. Gao2, Wei (Asian Journal of Chemistry, 2013)
For the quality assessment purposes, the paper reports a method for simultaneous determination of gallic acid and quercetin in P. niruri (Zhuzicao) by reversed phase high performance liquid chromatography (RP-HPLC) with ultraviolet light detection. Twenty-four samples from different source were planted in Xishuangbanna, China and then submitted to characters observation and quantitative determination. The average recoveries of gallic acid and quercetin were 96.66 % (RSD = 3.91 %) and 91.88 % (RSD = 2.69 %), respectively. The results indicated that there were distinct differences in the content of gallic acid and quercetin in P. niruri from different source and there were obvious correlation between botany characters and content. The method was simple and accurate with a good reproducibility and can be successfully applied to the quality assessment of P. niruri.